THE CORRELATION BETWEEN STUDENTS' LANGUAGE LEARNING STRATEGIES AND THEIR ENGLISH PROFICIENCY : (A PORTRAIT OF THE 10TH SEMESTER ENGLISH DEPARTMENT STUDENTS OF UPI) - Hasri Rediah Sopiani, - (2008)
English has been taught by Indonesian students as a second language since elementary school since it is an international language. However, English is felt as one of the difficult subjects to learn as most of Indonesian people use Bahasa Indonesia in daily life. Thus, language learning strategies are one of the ways to diminish this difficulty. Therefore, this study investigated whether or not there is correlation between students' language learning strategies and their English proficiency. It is also aimed to find out which kind of strategies the students most frequently used. This study employed descriptive method with an ex-post facto design. It also involved 30 the tenth semester students of English Department of Indonesia University of Education Bandung. The data were obtained through questionnaire, English proficiency documentary, and interview. The data were correlated using Pearson Product Moment Correlation statistical analysis through SPPS 15 for Windows while interview is used to strengthen the findings. The result shows that there was positive correlation between students' language learning strategies and their English proficiency (.702). It was also discovered that the intensity of using language learning strategies was medium. Besides, metacognitive strategies became the first rank (3.63), followed by compensation, social, cognitive, affective and memory strategies. This result meant that the higher students' language learning strategies intensity, the higher their English proficiency was. Moreover, this study revealed that language learning strategies were very good methods to make English students more proficient, autonomous and self directed. Finally, this study can be a useful source for English students who are going to improve their English proficiency and to be good language learners and for English teachers who are willing to help their students to be more autonomous students. Hence, it will be better if students and teachers are cooperative in improving language learning strategies usage.